The Impact of the Tourism Industry on Children's Education in A Marginalised Community: A Study on Perhentian Island, Terengganu, Malaysia - Norizan, Abdul Ghani; Hafiah, Yusof; Mohd Afandi, Salleh; Ruhaizan, Sulaiman@Abd. Rahim (2014)
The tourism industry is an important resource which could lead to prosperity and better living for the people, and education contributes significantly towards alleviation of poverty and reducing inequality in society. The objectives of this study are twofold. First, to examine the impact of the tourism industry on children’s education on Perhentian Island, Terengganu and second, to better know what the children think about tourism and education. A qualitative method has been used in this study using observation, interview and Focus Group Discussion (FGD) techniques. Prior research has revealed that the education level of a majority of the islanders, mainly the first and second generation settlers, is at a low 1level. Interviews revealed that less than 10 percent of third generation islanders are entering school at the tertiary level. Observation and interviews clearly showed that the vast development of the tourism industry contributed to the involvement of a majority of the school leavers in the industry. They became involved in low level jobs such as cleaners, receptionists, waitress, boatmen, tourist guides and micro business entrepreneurs.